2010
DOI: 10.1038/cddis.2010.46
|View full text |Cite
|
Sign up to set email alerts
|

Exploring ultrashort high-energy electron-induced damage in human carcinoma cells

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 15 publications
1
41
0
1
Order By: Relevance
“…This could benefit intensity modulated treatment where high lateral resolution is necessary. It has been shown that the range of energy, the charge per bunch, and the repetition rate of the laser satisfy many of the medical requirements for this application [84][85][86][87][88]. Monte Carlo calculations have been found to be in very good agreement with dose measurements.…”
Section: Laboratoire D'optique Appliquée-loa Palaiseau Francesupporting
confidence: 61%
See 1 more Smart Citation
“…This could benefit intensity modulated treatment where high lateral resolution is necessary. It has been shown that the range of energy, the charge per bunch, and the repetition rate of the laser satisfy many of the medical requirements for this application [84][85][86][87][88]. Monte Carlo calculations have been found to be in very good agreement with dose measurements.…”
Section: Laboratoire D'optique Appliquée-loa Palaiseau Francesupporting
confidence: 61%
“…They have published extensively in this area, researching: (a) radiotherapy with laser-plasma accelerators [84] both experimentally and using Monte Carlo simulation of deposited dose; and (b) measuring high energy electron induced damage in human carcinoma cells with electron bunches of ultrashort duration [85]. Treatment planning for laser accelerated very high energy electrons (now known as VHEE) has been carried out for prostate cancer and it has been found that the target coverage is better than that with a clinically approved 6 MV photon plan [86].…”
Section: Laser Driven Electron Beams For Radiotherapymentioning
confidence: 99%
“…The radiobiological effects at ultrahigh dose-rates and ultrashort timescales must be known, and initial experiments have been performed. 24 The feasibility of radiation therapy using laser-accelerated electrons has previously been studied in simulations. The dosimetric properties of laser-accelerated electrons were studied for low-energies in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…There is a significant interest in radiotherapeutic application of electrons accelerated by high power lasers in gaseous targets. Laser‐plasma accelerators produce femtosecond electron bunches that are quasi mono‐energetic with energies in the range of tens of MeV up to a few GeV, and with a pulsed dose‐rate exceeding 10 13 Gy/s. Results have been recently reported on biological material irradiated with laser generated electrons both in vitro and in vivo.…”
Section: High Dose‐rate Radiation Sourcesmentioning
confidence: 99%